Liquid Crystalline Nanostructured Polymer Blends - Poletto, Fernanda S.; Montoro, Sérgio Roberto [UNESP]; Tebaldi, Marli Luiza (Elsevier, 2015)
Polymeric materials presenting liquid crystalline domains are attracting increasing attention from academia and industry due to their unique properties, particularly for optical applications and as components of high-strength fibers. Polymer liquid crystals (PLC) present remarkable characteristics because they feature properties of polymers with those of liquid crystals. The PCL materials usually contain relatively rigid and flexible sequences in the polymer chain. The rigid element in the chain is called mesogen, which is responsible for inducing self-assembly of the same mesophases found in low molecular mass liquid crystals under suitable temperature, pressure, and concentration conditions. The mesogen can be placed in the main chain, or in side chains, or in both. The position of the mesogen in the chain is strongly related to the resulting properties exhibited by the polymeric material. The ordered arrangement from the polymer network at the nanoscale size range can also be tailored by blending. Several polymer liquid crystals have been blended with many thermoplastics improving the characteristics of the material. In addition, some polymers containing mesogen sequences can act as compatibilizers for other polymers. Considering this, basic science aspects of polymer liquid crystals and their polymeric blends will be discussed with current examples of technological applications in different areas.
Keywords: Liquid crystal; Mesogen; Mesophase; Polymer blend; Polymer liquid crystal